PENGARUH DANA ALOKASI UMUM (DAU) DAN DANA TRANSFER KHUSUS (DTK) TERHADAP BELANJA MODAL DAN INDEKS PEMBANGUNAN MANUSIA (IPM) DI BEBERAPA DAERAH OTONOMI - Fajar Nurmansyah; Vivi Adeyani Tandean (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2023)
This research investigates the effect of the general allocation fund and the specific purpose grant on capital expenditure and the human development index in Indonesia's autonomous regions. 70 districts and cities make up the purposive sampling sample for this investigation during 2017–2021 (5 years) after fundamental changes to the budgeting classification of budget transfers to local government. General allocation funds, specific purpose grants, capital expenditures, and the human development index are the statistics that were employed. The data source was taken from the Central Bureau of Statistics (BPS) and the Ministry of Finance. The analysis in this work uses multiple linear regressions. The findings demonstrated that while the general allocation fund variable had an impact on capital expenditures, the specific purpose grant variable did not. The general allocation fund and the specific purpose grant variables also have an impact on the human development index.